Efektivitas Alokasi Dana Desa dalam Program Pengadaan Ambulance di Kecamatan Majauleng Kabupaten Wajo - Fatmasari, Fatmasari; Muhammadiah, Muhammadiah; Parawangi, Anwar (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study purposed to determine the effectiveness of the Village Fund Allocation in the Ambulance Procurement Program in Majauleng District, Wajo Regency. The number of informants in this study was 13 people. This study used the Budiani theory. This study used descriptive qualitative research. The results of this study on indicators of program effectiveness had been categorized quite well because they were running well. The accuracy of the targets of government programs with a budget that had been set in accordance with the main target of the community. The socialization carried out by the government went well, the dissemination was directly or in writing on the information board. The main objective of the holding of the program was the improvement in the field of health for the community, achievement was carried out with good cooperation for the community and the government was very necessary in achieving the goals to be achieved. Monitoring was carried out to see the success of the programs run by the government. Monitor in terms of service to the community and usedm in the community.